Linear Trend Regression Analysis On Gold Forecasting For Investment In Indonesia During The Covid-19 Pandemic - Nursyahraini Husen; Rais; Lilies Handayani (Tadulako Science and Technology Journal, 2022)
Linear trend regression is also known as straight line trend, is a form of linear trend, that is trend whose variable X is (Time Period) highest rank one. The purpose of this study is to look at the model and predict the amount of gold prices during the COVID-19 pandemic in Indonesia using the linear trend regression method. The results obtained for the model of the total price of gold during the COVID-19 pandemic in Indonesia are Y = 623584.1 + 6129.1X + . As for forecasting the amount of gold prices for investment during the COVID-19 pandemic in Indonesia for the next 6 months using the linear trend regression method, it increases every month, it can be concluded that gold is suitable for investment because the price tends to rise, especially during the Covid-19 pandemic in Indonesia.